MOST EFFICIENT PART OF A PLANT FOR BIOCHAR PRODUCTION - Surya Mol N V, Dr. Ushakumary E R, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The aim of the study was to examine the eﬃciency of different bio char parts as an adsorbent to remove the organophosphate pesticide (malathon) from water. Three types of adsorbents, namely water hyacinth leaves, water hyacinth stem, water hyacinth root were prepared. Biochar is a powder material having carbon-rich form of charcoal derived by pyrolysis process at temperatures ranging from 300oC to 800oC under oxygen-limited conditions. Biochars shown effectiveness at removing heavy metals and organic pollutants from wastewaters through a process known as adsorption. Biochar produced from water hyacinth (Eichhornia crassipes) has been demonstrated to be a very effective adsorbent for removal of some heavy metals and pesticide and also as a means of control for this highly invasive species. In this study we find out which part of a plant is best biochar which will adsorb more pesticide from water using HPLC.